Analysis of Business Feasibility of Vegetable Traders In Kendari City - Sadimantara, Fahria Nadiryati; Rianse, Ilma Sarimustaqiyma; Syahrir, Syahrir (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
The objectives of this research are to analyze the business feasibility of traveling vegetable traders in Kendari City. Determination of research respondents in traveling vegetable traders conducted by accidental sampling. The determination method found as many as 30 traveling vegetable traders used as a sample. The data analysis method uses income analysis and the R/C ratio. The results showed that (1) the average amount of income of traveling vegetable traders were Rp81.191/day and Rp9.021,22/hour. (2) the average R/C ratio of the traveling vegetable traders is 1,43 which is greater than 1. It is concluded that the business of the traveling vegetable traders in Kendari City is worth continuing.